Antiadherent and Antibiofilm Activity of Humulus lupulus L. Derived Products: New Pharmacological Properties. (23rd September 2013) - Rozalski, Marcin; Micota, Bartlomiej; Sadowska, Beata; Stochmal, Anna; Jedrejek, Dariusz; Wieckowska-Szakiel, Marzena; Rozalska, Barbara
Abstract : New antimicrobial properties of products derived from Humulus lupulus L. such as antiadherent and antibiofilm activities were evaluated. The growth of gram-positive but not gram-negative bacteria was inhibited to different extents by these compounds. An extract of hop cones containing 51% xanthohumol was slightly less active against S. aureus strains (MIC range 31.2–125.0  μ g/mL) than pure xanthohumol (MIC range 15.6–62.5  μ g/mL). The spent hop extract, free of xanthohumol, exhibited lower but still relevant activity (MIC range 1-2 mg/mL). There were positive coactions of hop cone, spent hop extracts, and xanthohumol with oxacillin against MSSA and with linezolid against MSSA and MRSA. Plant compounds in the culture medium at sub-MIC concentrations decreased the adhesion of Staphylococci to abiotic surfaces, which in turn caused inhibition of biofilm formation. The rate of mature biofilm eradication by these products was significant. The spent hop extract at MIC reduced biofilm viability by 42.8%, the hop cone extract by 74.8%, and pure xanthohumol by 86.5%. When the hop cone extract or xanthohumol concentration was increased, almost complete biofilm eradication was achieved (97–99%). This study reveals the potent antibiofilm activity of hop-derived compounds for the first time.